DO PEER BANKS MATTER? IDENTIFYING PEER EFFECTS IN LIQUIDITY HOARDING BEHAVIOR IN INDONESIA - Sekar Satiti; Zaafri Ananto Husodo (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This paper examines the influence of peer effects on liquidity hoarding behavior and banking stability in Indonesia from 2018 to 2025. Using panel data from 44 banks categorized according to the KBMI classification, the estimation results reveal the presence of interbank contagion in liquidity hoarding, whereby banks adjust their liquidity buffers in response to the behavior of other banks. Furthermore, liquidity hoarding has a significantly negative effect on bank stability, as measured by the Z-score, indicating a defensive response by banks amid heightened uncertainty. These findings underscore the importance of monitoring systemic liquidity interactions across banks within Indonesia’s financial system.